Evolution of decorative elegance: rediscovering the honeysuckle pattern in the caisson ceilings of the Mogao Grottoes during the Middle Sui Dynasty/ Sujuan Kang, Nur Hisham Ibrahim and Muhamad Abdul Aziz Ab. Gani - Kang, Sujuan; Ibrahim, Nur Hisham; Ab. Gani, Muhamad Abdul Aziz (Universiti Teknologi MARA, Perak, 2023)
The Mogao Grottoes, situated in Dunhuang City, Gansu Province, holds significant cultural value as an iconic site of Chinese heritage. Among the intricate patterns adorning the caisson ceilings within these grottoes, the honeysuckle pattern stands out as one of the most popular designs. This paper proposes an innovative redesign method the honeysuckle pattern specifically for the caisson in the Mogao Grottoes during the middle Sui Dynasty in order to better inherit the art of Dunhuang and meet contemporary aesthetic requirements. A literature review and case study were used to summarize Lotus pattern types and characteristics. It begins by providing an overview of the original honeysuckle pattern found in the caisson ceilings of the grottoes, followed by an analysis of the different decorative patterns on the borders of caisson ceilings in the early and middle Sui dynasties. Then, paper proposes a novel design model for the honeysuckle pattern, drawing inspiration from historical designs and employing a combination of traditional and modern technology. Through this methodology, the paper concludes that the innovative honeysuckle pattern design for the caisson in the Mogao Grottoes successfully integrates traditional design elements with contemporary design methods. This design method not only reflects the historical context of the Middle Sui Dynasty but also exemplifies the potential of method in contemporary design practice.